The Achilles' heel of iron-based catalysts during oxygen reduction in an acidic medium - Choi, Chang Hyuck; Lim, Hyung-Kyu; Chung, Min Wook; Chon, Gajeon; Sahraie, Nastaran Ranjbar; Altin, Abdulrahman; Sougrati, Moulay-Tahar; Stievano, Lorenzo; Oh, Hyun Seok; Park, Eun Soo; Luo, Fang; Strasser, Peter; et al. (Energy and Environmental Science, 2018)
For catalysing dioxygen reduction, iron-nitrogen-carbon (Fe-N-C) materials are today the best candidates to replace platinum in proton-exchange membrane fuel cell (PEMFC) cathodes. Despite tremendous progress in their activity and site-structure understanding, improved durability is critically needed but challenged by insufficient understanding of their degradation mechanisms during operation. Here, we show that FeNxCy moieties in a representative Fe-N-C catalyst are structurally stable but electrochemically unstable when exposed in an acidic medium to H2O2, the main oxygen reduction reaction (ORR) byproduct. We reveal that exposure to H2O2 leaves iron-based catalytic sites untouched but decreases their turnover frequency (TOF) via oxidation of the carbon surface, leading to weakened O-2-binding on iron-based sites. Their TOF is recovered upon electrochemical reduction of the carbon surface, demonstrating the proposed deactivation mechanism. Our results reveal for the first time a hitherto unsuspected key deactivation mechanism during the ORR in an acidic medium. This study identifies the N-doped carbon surface as the Achilles' heel during ORR catalysis in PEMFCs. Observed in acidic but not in alkaline electrolytes, these insights suggest that durable Fe-N-C catalysts are within reach for PEMFCs if rational strategies minimizing the amount of H2O2 or reactive oxygen species (ROS) produced during the ORR are developed.